Effective Cross-National Respectful Partnerships: A Case Study of Peace Corps' Volunteer Covid-19 Volunteer Evacuation - Jody K. Olsen (Ubiquity Press, 2022)
Strong, trusted partnerships within a social capital framework are core to Peace Corps' successful international, national, and community interactions and outcomes. The Peace Corps' integrated three level model has thrived since its beginning in 1961. During this time, about 250 000 two-year Volunteers have lived and worked in 142 countries. In March 2020, the Peace Corps had to evacuate all 7 000 currently serving Volunteers because of the world-wide Covid-19 pandemic, a task organized and completed in nine days. The evacuation's success depended on the resiliency of these honored long-term partnerships, and specifically: a partnership model with three intertwining layers of collaboration between national and host country staff and Volunteers; years of respectful integration of Volunteers in local communities building mutual trust; in-country and cross-nation preparedness for health, safety, and security emergencies; transparent communication during the evacuation among all involved parties in every nation with Volunteers; and in-country and host country staff support across countries during the evacuation. This case study illustrates elements of effective and sustainable partnerships that ensure their effectiveness during a crisis and survival beyond the crisis. I write this at the anniversary of one year from my stepping down as the twentieth Director of the Peace Corps. During my tenure, I brought home all 7 000 currently serving Volunteers in nine days as the Covid-19 pandemic spread across countries. This massive - and successful - undertaking was possible because of long-standing and trusted partnerships between the Peace Corps and the communities and countries hosting Peace Corps Volunteers. This is my personal reflection and a reminder to build, honor, and tend relationships with international partners who are collaborators in learning, service, and research in good times and our friends, protectors, and allies in times of crisis.